Late presentation of turner syndrome and its complications / Huzairi Sani and Nada Syazana Zulkufli. - Sani, Huzairi; Zulkufli, Nada Syazana (Universiti Teknologi MARA Cawangan Selangor, 2018)
Turner syndrome is one of the most common sex chromosome abnormalities with an estimated true prevalence of 1 in 2,000 in newborns. This case report is of a girl who presented to the adult endocrinologist at 16 years of age and subsequently diagnosed with Turner syndrome. Despite frequenting clinics for unrelated ailments, her short stature was overlooked hence not investigated for a causative pathology. The aim of this report is to explore the diagnostics of Turner syndrome, hormone treatments available and the importance of starting treatment early.